Reduksi Noise Salt And Pepper Pada Citra Pankromatik Menggunakan Metode Contraharmonic Mean Filter - Sabry Mitra (STMIK Budi Darma, 2021)
A panchromatic image is an image that uses the entire spectrum visible to the eye from red to purple. The capture power of a panchromatic image recording device is almost the same as the sensitivity of the human eye. Taking images or pictures when using a camera often experiences noise or noise in the image caused by a bad camera lens or camera position when taking images so that it can cause noise in the image. resulting from. Noise or noise in the image greatly affects the clarity of an image where the image results are less clear when seen by the eye, therefore noise in the image must be removed so that the image can be clearer and have much better quality. The contraharmonic mean filter method is a filtering technique that works by replacing the intensity of a pixel with the average pixel value of the neighboring pixels, with the contraharmonic noise method in the image can be reduced so that the image is clearer than before. The contraharmonic method is very well used to remove noise in the panchromatic image so that the noise in the panchromatic image can be reduced by using the contraharmonic method which has a good role in reducing salt and pepper noise